Pengaruh Perbandingan Secondary Sheave Spring Standard Dan Racing Terhadap Akselerasi - Amin Nur Akhmadi; Mukhamad Khumaidi Usman; M. Taufik Qurohman (Fakultas Teknik UMSU, 2021)
Currently, automotive products, especially two-wheelers (motorbikes), are equipped with an automatic transmission system. The type of automatic transmission used is CVT (Continously Variable Transmission). Motorbikes with automatic transmission have several advantages, one of which is that they are more practical in use compared to motorbikes with manual transmission. The purpose of this study was to determine the RPM results on the effect of per cvt standard (1000 rpm) and per cvt racing (2000 rpm) on the RPM of a 2015 Honda Beat FI motorcycle. After replacing per cvt, it is expected to improve the performance of the 4 stroke combustion motor. The research method used is an experimental method, namely by starting the engine and holding the throttle at 1600 RPM after stabilizing then the throttle is rotated spontaneously up to 9000 RPM. The results of this study can be concluded that using per cvt2000 rpm only gets good acceleration and RPM at low rotational speeds. Whereas at high rotational speed it is less than optimal, but gets maximum power.